Analyzing volatility of rice price in Indonesia using ARCH/GARCH model - Ahmad Muslim (Economic Journal of Emerging Markets, 2014)
This research aims to to analyze and to study the implication of the volatility of deflated retail price of rice in out of Java which are represented by three markets in Indonesia, namely Medan, Makassar, and Banjarmasin. The period of observation is from January 1984 to August 2011. The better model in this study is Generalized Autoregressive Conditional Heteroskedasticity (GARCH). The result of the study shows that the change of rice price in all three markets was caused mainly by seasons and yearly routine cycles. In addition, at the reformation era and at economic crisis, the rice prices were more volatile.